2016
DOI: 10.7160/eriesj.2016.090101
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Results Obtained by Students of Different Faculties

Abstract: The paper presents and discusses the results of statistical analysis of differences among scores obtained by students of different faculties of the University of Economics in Prague. The analysed dataset contains the scores for 2256 students that took basic mathematics course during the academic year 2013/2014. A two way analysis of variance was performed with semester and faculty as main factors. The interaction between these two factors was also considered. Students have to take two tests. At first, the sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…From the results it can be observed that students tend to score better in the summer semester than in winter semester in each academic year. This finding supports the conclusions from papers written in previous years [8], [9], which were based on data from one academic year only. Moreover, the effect of semester is statistically significant in both models (mid-term test score and final test score).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…From the results it can be observed that students tend to score better in the summer semester than in winter semester in each academic year. This finding supports the conclusions from papers written in previous years [8], [9], which were based on data from one academic year only. Moreover, the effect of semester is statistically significant in both models (mid-term test score and final test score).…”
Section: Discussionsupporting
confidence: 90%
“…An extensive analysis was conducted by Ulrychová in [12], who analysed differences in mathematics results between students of University of Economics, Prague and students of the University of Finance and Administration in Prague. We analysed the differences between performance of students coming from different faculties of the University of Economics [8] and we also discussed the impact of exam date on the performance [9].…”
Section: Motivation and Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of motivation to study and the insufficient level of mathematical knowledge from primary and secondary schools rank among the most serious causes. This paper was motivated by articles [2][3][8][9][10][11], where the decreasing level of knowledge was discussed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting is paper [9], where they investigate influences of the fail-rates of students who studied on a Bachelors´ degree programme at the selected university. In [11], the differences between the scores obtained by the students of different faculties are discussed.…”
Section: Introductionmentioning
confidence: 99%